RETRACTED: AUTHENTIC HAPPINESS OF NUN WHO HAVE MUSLIM PARENTS - Riskasari, Windah (Psikis : Jurnal Psikologi Islami, 2023)
Retraction Notice: Following reports expressed by a third party via emailat psikis@radenfatah.ac.id about the infringements of professional ethical codesand a considered review of the article entitled "Authentic Happiness of Nuns WhoHave Muslim Parents” in Volume 9, No. 1, June 2023. The editorial team thoroughlyinvestigated the alleged violation and notified the author, along with the proof.Based on the discussion between the editorial team and the editorial advisoryboard on January 22, the article has violated the code of ethics. This articleviolates inappropriate authorship. Therefore, The editors retracted the articledue to the author violated publication ethics.